Determination of biogenic amines in seawater using capillary electrophoresis with capacitively coupled contactless conductivity detection - Gubartallah, E.A. (MDPI AG, 2018)
A rapid and green analytical method based on capillary electrophoresis with capacitively coupled contactless conductivity detection (C4D) for the determination of eight environmental pollutants, the biogenic amines (putrescine, cadaverine, spermidine, spermine, tyramine, 2-phenylamine, histamine and tryptamine), is described. The separation was achieved under normal polarity mode at 24 â¦C and 25 kV with a hydrodynamic injection (50 mbar for 5 s) and using a bare fused-silica capillary (95 cm length Ã 50 Âµm i.d.) (detection length of 10.5 cm from the outlet end of the capillary). The optimized background electrolyte consisted of 400 mM malic acid. C4D parameters were set at a fixed amplitude (50 V) and frequency (600 kHz). Under the optimum conditions, the method exhibited good linearity over the range of 1.0â100 Âµg mLâ 1 (R2 â¥ 0.981). The limits of detection based on signal to noise (S/N) ratios of 3 and 10 were â¤0.029 Âµg mLâ 1. The method was used for the determination of seawater samples that were spiked with biogenic amines. Good recoveries (77â93) were found. Â© 2018 by the authors.